Pijat Oksitosin terhadap Volume ASI di PMB E Kota Palangka Raya - Herlinadiyanigsih, Herlinadiyanigsih; Ruttata, Peni (Jurnal Kebidanan Malakbi, 2021)
Breastmilk (ASI) is the first, main and best food for neonates, which is natural and contains various nutrients needed in the process of baby growth and development. Lack of milk production is one of the reasons why mothers give formula milk to their babies. Oxytocin massage is a massage along the spine (vertebrae) to the fifth-sixth rib and is an attempt to stimulate the hormones prolactin and oxytocin after childbirth. The purpose of this study was to determine the effect of oxytocin massage on breast milk volume. This research design is quasy experiment with post test design. The population of this study was 78 post-partum mothers with a total sample of 26 post-partum mothers who met the inclusion and exclusion criteria using purposive sampling technique. The data collection method is by pumping breast milk and measuring it using a measuring cup and observation sheet. This research was conducted in February – April 2019 at the Independent Practice of Midwives E, Palangka Raya City. Data analysis used Man-Whitney. The results showed that the average value of breastfeeding volume was 21,369 in the cc intervention group and the average value of breast milk volume was 19,385 cc in the control group. The results of statistical analysis obtained a P-value of 0.840. The conclusion of this study is that there is no significant difference in the volume of breastmilk between oxytocin massage and oxytocin massage at the Bidan E Practice, Palangka Raya City. Research is needed relating to other factors that can increase the amount of milk production.